SOME CURRENT ISSUES OF THE USE OF INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Fakhriddin Urinboev Toshboltaev; Ikromaliyeva Gulsevar Muzaffar qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article examines the current issues surrounding the integration of information technologies (IT) into the educational process. It highlights both the opportunities and challenges that arise from using digital tools, such as e-learning platforms, virtual classrooms, and educational software, in modern education systems. The paper discusses the digital divide, data privacy concerns, teacher training, and the potential impact of IT on traditional teaching methods. Additionally, it explores the role of technology in promoting personalized learning, improving access to education, and fostering collaboration in a globalized learning environment. The article offers a critical analysis of how these issues can be addressed to ensurAve the effective and equitable use of information technologies in education.